Sustainable cities - response to urban environmental problems - Žagar, Ksenija (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
Urban areas have considerable impact on the environment, which is reflected on the global level, but at the same time face many environmental problems. Sustainable cities proceed from the need to improve the quality of city life and incorporate all components of sustainable development. On the example of Waitakere city, New Zealand, the article studies the main environmental problems and analyses measures introduced by the city for the improvement of the state of the environment in the city.
Keywords: ecology; ekologija; ekologija mest; environmental protection; geografija naselij; mesta; New Zealand; Nova Zelandija; settlement geography; sonaravni razvoj; sustainable development; urban ecology; urban geography; urbanizacija; urbanization; varstvo okolja